2020
DOI: 10.3390/nu12020356
|View full text |Cite
|
Sign up to set email alerts
|

Biological Role of Unsaturated Fatty Acid Desaturases in Health and Disease

Abstract: Polyunsaturated fatty acids (PUFAs) are considered one of the most important components of cells that influence normal development and function of many organisms, both eukaryotes and prokaryotes. Unsaturated fatty acid desaturases play a crucial role in the synthesis of PUFAs, inserting additional unsaturated bonds into the acyl chain. The level of expression and activity of different types of desaturases determines profiles of PUFAs. It is well recognized that qualitative and quantitative changes in the PUFA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 228 publications
(173 reference statements)
1
61
1
2
Order By: Relevance
“…In infants, the demand for PUFA is different from adults. Moreover, the genetic makeup may contribute to differences in plasma lipid profiles, since single nucleotide polymorphisms (SNPs) in FADS genes can modulate desaturase activity [30] . Furthermore, pre- (maternal) and postnatal feeding could influence circulating desaturase activity markers.…”
Section: Discussionmentioning
confidence: 99%
“…In infants, the demand for PUFA is different from adults. Moreover, the genetic makeup may contribute to differences in plasma lipid profiles, since single nucleotide polymorphisms (SNPs) in FADS genes can modulate desaturase activity [30] . Furthermore, pre- (maternal) and postnatal feeding could influence circulating desaturase activity markers.…”
Section: Discussionmentioning
confidence: 99%
“…In fatty acid synthesis, both ChREBP and SREBP-1c induce Acc , which encodes an enzyme that is required for the conversion of acetyl CoA to malonyl CoA, and Fasn , which encodes an enzyme that is required for the production of palmitoyl CoA from malonyl CoA and acetyl CoA ( 9 , 10 , 13 , 34 , 51 ). In fatty acid elongation and desaturation, ChREBP induces the expression of the stearoyl CoA desaturase-1 gene ( Scd-1 ) and Elovl6 , both of which are required for the synthesis of monounsaturated fatty acids (MUFAs), while SREBP-1c induces Elovl2 , fatty acid desaturase 1, and fatty acid desaturase 2, which are required for the synthesis of polyunsaturated fatty acids (PUFAs), as well as Scd-1 and Elovl6 ( Figure 2 ) ( 52 56 ). Consistent with this, hepatic Chrebp overexpression reduces the concentrations of saturated fatty acids (SFAs), such as palmitic acid (C16:0) and stearic acid (C18:0); and increases that of the MUFA oleic acid (C18:1 n-9) ( 32 , 57 ).…”
Section: Carbohydrate Response Element-binding Protein Regulates Hepamentioning
confidence: 99%
“…The results of some studies suggested that the intake of linoleic acid (C18: 2n-6), palmitic acid, and oleic acid which esterified in the sn-2 position on triglycerides correlating to the levels of arachidonic acid (C20: 4n-6), palmitoleic acid (C16: 1n-7) and eicosatrienoic acid (C20: 3n-9) as a result of successive metabolism of linoleic acid, palmitic acid, and oleic acid. It can be seen from the reduced concentration of linoleic acid which is accompanied by increased concentration of arachidonic acid in plasma (Zhang et al 2016;Czumaj and Śledziński 2020). A similar case also occurred in the metabolism of fatty acids in the COST.…”
Section: Effect Of Co and Cost On Bdnf Serummentioning
confidence: 76%